Stalinism, its impact on Russia and the world - edited by G. R. Urban. (St. Martin's Press, 1982)
Based on RFE/RL "Third Programme" broadcasts. Participants: Boris Bazhanov, W. Averell Harriman, Theodor Prager, Adam B. Ulam, Robert C. Tucker, Milovan Djilas, Leszek Kolakowski, Roderick MacFarquhar, Bao Ruo-wang, George F. Kennan, Leonard Shapiro.